SOCIAL REPRESENTATIONS AND CRIMINALIZATION OF YOUTH IN CULIACÁN, MEXICO, 1994 - Bojórquez Luque, Jesús (2020)
The purpose of this paper is to examine, from the concept of social representations, the strategies of the municipal government of Culiacán in Mexico, in order to analyze the high index of insecurity at the beginning of 1994, where the authorities sought to diminish the freedoms of young people by trying to restrict their schedules on public roads, prohibit the use of miniskirts and necklines in girls and long hair in men. For the methodology, literature for the conceptual framework and for the background informationwas consulted, as well as newspapers that, at the time, provided testimonies of the problematic in the public sphere. The actions of young people forced the authorities toreverse the tactics implemented to overcome insecurity.